PERLINDUNGAN PEKERJA RUMAH TANGGA (PRT) MELALUI KEPASTIAN HUKUM DI INDONESIA DAN HUKUM ISLAM - Yasirwan Yasirwan; Muhammad Hafiz Ikhsan; Nikmah Dalimunthe (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2023)
Domestic workers are often known as helpers, not as workers who are the same as others. Domestic workers are usually performed by women, and Islam itself does not prohibit women from becoming workers. The problems that are often experienced by domestic workers in Indonesia are working hours and wages, as well as violence perpetrated by employers. In Islam, wages must be paid according to the agreement and workers should not be tortured. Due to the frequent occurrence of problems experienced by domestic workers due to the absence of a specific law that regulates domestic workers, this paper will discuss the protection of domestic workers through legal certainty in Indonesia and Islamic law. This article uses normative legal research methods, and the data source used is secondary data. The results of the research in the article show that the policy through the formation of the Law on the Protection of Domestic Workers is something that is really needed, because besides having the main goal of protecting domestic workers in Indonesia and in Islamic law, creating a sense of justice by giving wages and protecting domestic workers is a very important thing. needs to be done in this employment industry.